Loss of β-Cytoplasmic Actin in the Intestinal Epithelium Increases Gut Barrier Permeability in vivo and Exaggerates the Severity of Experimental Colitis - Lechuga, Susana; Naydenov, Nayden G.; Feygin, Alex; Cruise, Michael; Ervasti, James M.; Ivanov, Andrei I. (Frontiers in Cell and Developmental Biology, 2020)
Intestinal epithelial barrier is critical for the maintenance of normal gut homeostasis and disruption of this barrier may trigger or exaggerate mucosal inflammation. The actin cytoskeleton is a key regulator of barrier structure and function, controlling the assembly and permeability of epithelial adherens and tight junctions. Epithelial cells express two actin isoforms: a β-cytoplasmic actin and γ-cytoplasmic actin. Our previous in vitro studies demonstrated that these actin isoforms play distinctive roles in establishing the intestinal epithelial barrier, by controlling the organization of different junctional complexes. It remains unknown, whether β-actin and γ-actin have unique or redundant functions in regulating the gut barrier in vivo. To address this question, we selectively knocked out β-actin expression in mouse intestinal epithelium. Mice with intestinal epithelial knockout of β-actin do not display gastrointestinal abnormalities or gross alterations of colonic mucosal architecture. This could be due to compensatory upregulation of γ-actin expression. Despite such compensation, β-actin knockout mice demonstrate increased intestinal permeability. Furthermore, these animals show more severe clinical symptoms during dextran sodium sulfate induced colitis, compared to control littermates. Such exaggerated colitis is associated with the higher expression of inflammatory cytokines, increased macrophage infiltration in the gut, and accelerated mucosal cell death. Consistently, intestinal organoids generated from β-actin knockout mice are more sensitive to tumor necrosis factor induced cell death, ex vivo. Overall, our data suggests that β-actin functions as an essential regulator of gut barrier integrity in vivo, and plays a tissue protective role during mucosal injury and inflammation. (ZO) µ-catenin.